2011
DOI: 10.1186/1475-925x-10-10
|View full text |Cite
|
Sign up to set email alerts
|

Signal processing of heart signals for the quantification of non-deterministic events

Abstract: BackgroundHeart signals represent an important way to evaluate cardiovascular function and often what is desired is to quantify the level of some signal of interest against the louder backdrop of the beating of the heart itself. An example of this type of application is the quantification of cavitation in mechanical heart valve patients.MethodsAn algorithm is presented for the quantification of high-frequency, non-deterministic events such as cavitation from recorded signals. A closed-form mathematical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Wang et al [2] suggests that PCG signal S(n) can be modeled as shown in equation (3) S(n) = F(n)+O(n) = F(n)+C(n)+N(n) (3) where F(n) represents the fundamental components of the heart sounds S 1 and S 2 (SOI), and O(n) represents other sounds which can be decomposed into C(n), other heart sound components (such as murmurs, etc) and N(n), the noise component.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Wang et al [2] suggests that PCG signal S(n) can be modeled as shown in equation (3) S(n) = F(n)+O(n) = F(n)+C(n)+N(n) (3) where F(n) represents the fundamental components of the heart sounds S 1 and S 2 (SOI), and O(n) represents other sounds which can be decomposed into C(n), other heart sound components (such as murmurs, etc) and N(n), the noise component.…”
Section: Methodsmentioning
confidence: 99%
“…The non-deterministic energy of the signal with S1 peaks aligned [3] follows the Johansen algorithm [4] with the modification made in the segmentation algorithm [3]. By Johansen algorithm, the level of nondeterministic energy is defined as the difference between the deterministic energy and the total energy as in the following equation (8): (8) where the E non-det represents the non-deterministic energy of the signal which is the energy of interest.…”
Section: Non-deterministic Energy Calculationmentioning
confidence: 99%
See 3 more Smart Citations